Association of Delayed Antimicrobial Therapy with One-Year Mortality in Pediatric Sepsis. Issue 1 (July 2017) - Han, Moonjoo; Fitzgerald, Julie C.; Balamuth, Fran; Keele, Luke; Alpern, Elizabeth R.; Lavelle, Jane; Chilutti, Marianne; Grundmeier, Robert W.; Nadkarni, Vinay M.; Thomas, Neal J.; Weiss, Scott L.
ABSTRACT: Objective: Delayed antimicrobial therapy in sepsis is associated with increased hospital mortality, but the impact of antimicrobial timing on long-term outcomes is unknown. We tested the hypothesis that hourly delays to antimicrobial therapy are associated with 1-year mortality in pediatric severe sepsis. Design: Retrospective observational study. Setting: Quaternary academic pediatric intensive care unit (PICU) from February 1, 2012 to June 30, 2013. Patients: One hundred sixty patients aged ⩽21 years treated for severe sepsis. Interventions: None. Measurements and Main Results: We tested the association of hourly delays from sepsis recognition to antimicrobial administration with 1-year mortality using multivariable Cox and logistic regression. Overall 1-year mortality was 24% (39 patients), of whom 46% died after index PICU discharge. Median time from sepsis recognition to antimicrobial therapy was 137 min (IQR 65–287). After adjusting for severity of illness and comorbid conditions, hourly delays up to 3 h were not associated with 1-year mortality. However, increased 1-year mortality was evident in patients who received antimicrobials ⩽1 h (aOR 3.8, 95% CI 1.2, 11.7) or >3 h (aOR 3.5, 95% CI 1.3, 9.8) compared with patients who received antimicrobials within 1 to 3 h from sepsis recognition. For the subset of patients who survived index PICU admission, antimicrobial therapy ⩽1 h was also associated with increased 1-year mortality (aOR 5.5, 95% CI 1.1, 27.4), while antimicrobial therapy >3 h was not associated with 1-year mortality (aOR 2.2, 95% CI 0.5, 11.0). Conclusions: Hourly delays to antimicrobial therapy, up to 3 h, were not associated with 1-year mortality in pediatric severe sepsis in this study. The finding that antimicrobial therapy ⩽1 h from sepsis recognition was associated with increased 1-year mortality should be regarded as hypothesis-generating for future studies. Abstract : Supplemental Digital Content is available in the text